Enhancing financial oversight of the Public Accounts Commitee in the Nelson Mandela Bay Metropolitan Municipality - Motsilili, Chris (My University, 2017)
In recent years, increased attention being given to accountability on public finances in South African municipalities saw an increase in the number of municipalities establishing Municipal Public Accounts Committees (MPACs) to address deficiencies and gaps in the local government accountability mechanisms and oversight. The purpose of the study was to establish the alignment between the recently established MPACs and the generally accepted public accounts committees with respect to the institutional design, practices and performance assessment. A qualitative case study of the Nelson Mandela Bay Metropolitan Municipality (NMBM) MPAC was followed where documents were analysed and semi-structured in-depth interviews with purposively selected participants were conducted. This research study revealed some gaps in the alignment of the NMBM MPAC to the generally accepted public accounts committees. The most crucial gap that emerged pertained to the mandate and powers of the NMBM MPAC. Recommendations for enhancing the financial oversight of the NMBM MPAC were made. The study also suggests further research on a larger number of municipalities.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in 25% fulfilment of the requirements for the degree of Master of Management (in the field of Public and Development Management) March 2017
Keywords: Legislative oversight--South Africa; Finance, Public--South Africa; Municipal finance--South Africa